2022
DOI: 10.3389/fmicb.2022.1046733
|View full text |Cite
|
Sign up to set email alerts
|

Advances in microbial metagenomics and artificial intelligence analysis in forensic identification

Abstract: Microorganisms, which are widely distributed in nature and human body, show unique application value in forensic identification. Recent advances in high-throughput sequencing technology and significant reductions in analysis costs have markedly promoted the development of forensic microbiology and metagenomics. The rapid progression of artificial intelligence (AI) methods and computational approaches has shown their unique application value in forensics and their potential to address relevant forensic question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Metagenomics has defined the study of whole genetic material recovered directly from a sample and through sequencing of marker amplicons –metabarcoding– or whole DNA random fragmentation –shotgun– ( Garza and Dutilh, 2015 ). Recent advances in high-throughput sequencing and the considerable reduction of analysis costs have boosted the development of microbiology and metagenomics ( He et al, 2022 ). Next-generation sequencing (NGS) technologies have made it possible to improve the coverage and depth of studies, allowing the rigorous analysis of complex microbial communities ( Almeida and de Martinis, 2019 ).…”
Section: Metagenomic As Revolution Microbiome Study Approachmentioning
confidence: 99%
“…Metagenomics has defined the study of whole genetic material recovered directly from a sample and through sequencing of marker amplicons –metabarcoding– or whole DNA random fragmentation –shotgun– ( Garza and Dutilh, 2015 ). Recent advances in high-throughput sequencing and the considerable reduction of analysis costs have boosted the development of microbiology and metagenomics ( He et al, 2022 ). Next-generation sequencing (NGS) technologies have made it possible to improve the coverage and depth of studies, allowing the rigorous analysis of complex microbial communities ( Almeida and de Martinis, 2019 ).…”
Section: Metagenomic As Revolution Microbiome Study Approachmentioning
confidence: 99%
“…AI with machine learning already started transforming the field of forensic microbiology. Microbial succession during postmortem decay can be a promising tool for PMI detection [ 21 ]. Johnson et al have developed an AI algorithm to effectively investigate PMI by taking skin microbiota samples from nasal and ear canals [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Johnson et al have developed an AI algorithm to effectively investigate PMI by taking skin microbiota samples from nasal and ear canals [ 22 ]. Microbiome characterization can be a potential tool for performing one of the most critical tasks of individual identification, as, theoretically, every individual carries a unique set of microbial communities that remains relatively stable over long periods [ 21 ]. Yang et al identified individuals with an accuracy of 90% using random forest machine learning by integrating Cutibacterium acnes 16S rRNA genotype with skin microbiome profile data [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…It is widely recognized that microbiota can be utilized for PMI estimation [6][7][8][9][10][11][12][13][14]. During the fresh stage, cellular macromolecules are released shortly after death, and the microbiota play a crucial role in breaking down these macromolecules into simpler compounds [15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have conducted comprehensive investigations into microbial succession, focusing predominantly on murine models [8,13,[19][20][21][22][23][24][25], specifically rats and mice [2,26]. Metcalf et al found a "microbial clock" with the capacity to estimate the PMI with a margin of error approximating ±3 days [2], while the experiment was carried out under rigorously controlled circumstances, utilizing experimental mouse models, thus necessitating judicious interpretation when extrapolating these findings to authentic, realworld scenarios [27].…”
Section: Introductionmentioning
confidence: 99%